Strategic and sustainable human resource management: Twin weapon for achieving competitive advantage in organization - Gunawan, William Ben; Mikhail, Lukas (Priviet Social Sciences Journal, 2025)
This perspective explores the integration of strategic human resource management (strategic HRM) and sustainable human resource management (sustainable HRM) as a dual strategy for organizational competitive advantage. Strategic HRM focuses on aligning HR policies with business goals to maximize employee engagement, innovation, and productivity, thereby enhancing organizational performance. Key strategic HRM practices include performance management, talent development, and fostering a cohesive company culture that values inclusivity and adaptability. However, strategic HRM’s strategic focus often prioritizes immediate organizational needs over long-term societal concerns. In contrast, sustainable HRM emphasizes a broader, long-term perspective, addressing economic, social, and environmental impacts. This approach integrates multi-stakeholder engagement, ethical practices, and a commitment to societal well-being, thus ensuring the organization’s resilience and sustainability. The research highlights the evolving nature of HRM, noting that the contemporary business landscape requires organizations to balance financial success with social responsibility and environmental stewardship. The findings underscore the complementary nature of strategic HRM and sustainable HRM. While strategic HRM drives performance and competitive advantage, sustainable HRM ensures ethical governance and societal impact. Implementing both approaches enhances organizational adaptability, employee satisfaction, and long-term success. This paper concludes with strategic recommendations for HR leaders, emphasizing the need for strategic alignment, stakeholder engagement, and flexible HR practices that promote both organizational excellence and sustainability.